Factors affecting mitochondrial efficiency - Joyce, Oliver James Patrick (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2004)
Experiments were designed to investigate for the first time in situ synaptosomal mitochondrial bioenergetic function using synaptosomes prepared from the whole brain of rats and to compare bioenergetic functions in synaptosomes isolated from young (3 month) and old (24 month) whole rat brain. The investigation describes for the first time the pattern of control of mitochondrial energy metabolism based on the kinetic responses of the substrate oxidation, proton leak and phosphorylation systems to changes in the mitochondrial membrane potential (ΔΨM) in synaptosomes isolated from the whole brain of rat. in addition, a comparison was made of the aforementioned kinetic responses, in synaptosomes isolated from old and young animals.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin